Makna Leksikon Budidaya Tambak sebagai Representasi Kearifan Lokal dan Harmoni Ekologis Masyarakat Desa Wedani, Gresik: Kajian Antropolinguistik - Shinta, Kharisma; Zakiyah, Millatuz (Kajian Linguistik dan Sastra, 2024)
The community of Gresik, particularly in Desa Wedani, has a rich lexicon related to fish pond cultivation. This study aims to: (1) describe the morphological formation process of fish farming lexicon in the local community; (2) analyze the structure and formation of phrases within the lexicon; (3) identify the cultural meanings and social aspects that influence the formation and usage of lexicon in freshwater fish farming in Desa Wedani. This research uses a qualitative descriptive approach with data collection methods including observation, interviews, and documentation. Data analysis employs semantic and anthropolinguistic analysis to understand the relationship between language, culture and social practices of the community. The findings show that the morphological formation process involves the addition of prefixes, such as ng-, ny-, and nj-, to base words to create active verbs referring to specific activities in fish farming. Lexicon data found include ngeduk (lifting soil at the pond's edge), nyingkal (tilling the soil to improve water circulation) and ngipuk (sifting to protect fish fry). The structure and formation of phrases within the lexicon demonstrate a close link between farming activities and the local language. The cultural meanings embedded in this lexicon reveal social values such as the community's attachment to environmental conservation and local wisdom in managing natural resources. The results of this study can enrich linguistic and anthropological language studies and support efforts to preserve local language and culture.